Histoplasma capsulatum in the bone marrow of an HIV-infected patient - Medina Piñón, Isaí; Hernández Rodríguez, Pedro; Haces Rodríguez, Silvia Estela; Acosta Calderón, Luis Arturo (2017)
A 41-year-old man was admitted to the emergency department with a 1-month history of weight loss, intermittent fever, and malaise. Generalized pallor, mild dehydration, and a temperature of 37.5 C were found on physical examination. Initial blood workup revealed pancytopenia, elevated lactate dehydrogenase, and hypoalbuminemia. A fourth-generation HIV ELISA test was positive. His HIV-1 RNA viral load was 13 800 copies/ml and the CD4+ T-cell count was 3 cells/mm3 . Urine, blood, and cerebrospinal fluid cultures were without microbiological isolation